2016
DOI: 10.1016/j.ijcard.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal atrial fibrillation and the hazards of under-treatment

Abstract: Background and Purpose Oral anticoagulants are highly efficacious for the prevention of stroke in atrial fibrillation, and are the preferred treatment by current guidelines. The purpose of our study was to assess the utilization of antithrombotic drugs in atrial fibrillation patients at the time of ischemic stroke and the factors associated with their use. Methods We enrolled 759 consecutive patients admitted with ischemic stroke at Boston Medical Center, Geisinger Health System, and the University of Alabam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
4
16
4
Order By: Relevance
“…The guideline on AF management recommended OAC for stroke prevention, irrespective of the type of AF [8]. Aronis et al in 2016 [34] and Rizos et al [35] in 2011 reported that a significant proportion of episodes of stroke in patients with AF occur in patients with a history of paroxysmal AF, varying from 31 to 53%. In view of this, physicians should pay more attention to patients with paroxysmal or persistent AF.…”
Section: Duration and Type Of Afmentioning
confidence: 99%
“…The guideline on AF management recommended OAC for stroke prevention, irrespective of the type of AF [8]. Aronis et al in 2016 [34] and Rizos et al [35] in 2011 reported that a significant proportion of episodes of stroke in patients with AF occur in patients with a history of paroxysmal AF, varying from 31 to 53%. In view of this, physicians should pay more attention to patients with paroxysmal or persistent AF.…”
Section: Duration and Type Of Afmentioning
confidence: 99%
“…Yet, most studies defined PAF as events lasting more than 30 seconds, derived from the AHA 2006 guidelines [ 10 ]. PAF is a self-promoting process that can progress to persistent AF if left undetected and untreated with rhythm control and anticoagulation [ 27 ]. In AF, diminished blood flow within the complex trabeculated anatomy of the left atrial appendage (LAA) promotes thrombus formation with associated inflammation, leading to stroke by embolization [ 28 ].…”
Section: Paroxysmal Atrial Fibrillation and Strokementioning
confidence: 99%
“…Underutilisation of anticoagulation, particularly in the older population, has been reported in several studies. 7 - 9 Appropriate anticoagulation is particularly important among older persons since this patient group is at greater risk of stroke attributable to AF. 22 Recurrent falls or a high risk for falls was a common reason for withholding anticoagulation therapy in the study population as has been reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 3 , 4 , 5 Although recent data shows good progress in the management of patients with AF, there is still substantial evidence of suboptimal therapy. 6 , 7 , 8 9 …”
Section: Introductionmentioning
confidence: 99%